From Data to Decisions: The Impact of AI in Modern Healthcare - Gopkumar, Ashwin S; Singh, Sonu Kumar (Journal of Advanced Research in Signal Processing and Applications, 2025)
Artificial intelligence (AI) is revolutionising healthcare by enhancing diagnostics, personalised medicine, and administrative efficiency. Leveraging advanced techniques such as machine learning, neural networks, and natural language processing, AI systems outperform traditional methods in tasks like medical imaging, disease prediction, and clinical decision support. However, challenges such as explainability, data privacy, ethical considerations, and integration into existing workflows limit widespread adoption. This paper explores the applications of AI in healthcare, its benefits, and the associated barriers, emphasising the need for transparent, ethical, and patient-centric AI systems. Addressing these challenges can unlock AI’s full potential to improve healthcare outcomes and accessibility globally.